Optical mapping of single-molecule human DNA in disposable, mass-produced all-polymer devices. (26th August 2015) - Østergaard, Peter Friis; Lopacinska-Jørgensen, Joanna; Pedersen, Jonas Nyvold; Tommerup, Niels; Kristensen, Anders; Flyvbjerg, Henrik; Silahtaroglu, Asli; Marie, Rodolphe; Taboryski, Rafael
Abstract: We demonstrate all-polymer injection molded devices for optical mapping of denaturation–renaturation (DR) patterns on long, single DNA-molecules from the human genome. The devices have channels with ultra-low aspect ratio, only 110 nm deep while 20 μ m wide, and are superior to the silica devices used previously in the field. With these polymer devices, we demonstrate on-chip recording of DR images of DNA-molecules stretched to more than 95% of their contour length. The stretching is done by opposing flows Marie et al (2013 Proc. Natl Acad. Sci. USA 110 4893–8). The performance is validated by mapping 20 out of 24 Mbp-long DNA fragments to the human reference genome. We optimized fabrication of the devices to a yield exceeding 95%. This permits a substantial economies-of-scale driven cost-reduction, leading to device costs as low as 3 USD per device, about a factor 70 lower than the cost of silica devices. This lowers the barrier to a wide use of DR mapping of native, megabase-size DNA molecules, which has a huge potential as a complementary method to next-generation sequencing.